Uncertainty in economics : and other reflections - Shackle, G. L. S. (Cambridge, Eng. : University Press, 1955)
This book is a collection of some of Professor Shackle's papers written between 1939 and 1953 is largely concerned with the problems of 'expectation' and 'uncertainty' and with reducing these universal factors to some sort of plausible rules. Also included are essays on interest rates, on investment and employment, and on the philosophy of economics. This book, by one of the finest economic writers of his time, will appeal to anyone with an interest in the history of economics.
Includes bibliographical references and index.
rpm 05/04/2018
Loans
Keywords: Economics